PEMANFAATAN PAPAN INFORMASI DIGITAL (PID) UNTUK MENDUKUNG PEMBELAJARAN BERBASIS DEEP LEARNING DAN TPACK PADA SISWA SEKOLAH DASAR - Andhiny, Restu; Purbonuswanto, Welius; Rejokirono; Dwi Hartanti, Christina; Zakariyah, Yogi Aldias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of educational technology encourages elementary schools to create innovative and adaptive learning practices that meet the needs of 21st century education. One form of this innovation is the use of PID as both information media and learning media within the school environment. This study aims to describe the utilization of PID in supporting Deep Learning-based instruction and the TPACK approach for students at SD Negeri Jetis. The study employed a descriptive qualitative method involving principals teachers and students as research subjects. Data collection techniques included observation interviews and documentation. The findings revealed that PID was utilized as interactive learning media and digital literacy media. In supporting Deep Learning PID helped create meaningful contextual, collaborative learning experiences, and encouraged students critical thinking skills through educational videos animated visuals group discussions and project-based learning activities. From the TPACK perspective the use of PID assisted teachers in integrating technology pedagogy and learning content more effectively making the learning process more engaging active and enjoyable. The implementation of PID also increased students’ learning motivation participation and creativity in classroom activities. School support for technology integration and students’ enthusiasm became important supporting factors in the implementation of PID. Several obstacles were identified including unstable internet connections teachers’ limited ability in developing digital content and the less optimal management of PID materials. This study concludes that PID plays an important role in supporting the transformation of 21st century learning in elementary schools toward innovative interactive and student centered learning